Effect of rejuvenators on penetration and softening poind of aged polymer-modified road bitumen - Audrius Vaitkus (Vilnius Gediminas Technical University, 2021)
The article describes the effiency of polymer-modified road bitumen regeneration with two types of rejuvenators. Two alternative rejuvenators have been selected aromatic oil Nygen 910 and soft road bitumen V12000. PMB 45/80-55 bitumen, which is used in the upper and lower layers of asphalt pavement, was investigated. During the life time of the asphalt pvement, due to the effects of solar UV radiation, temperature and oxygen, of all the layers of the structure asphalt top layer reaches the highest degree of aging. Short-term and long-term aging were performed to simulate the aging of the bitmen under laboratory conditions. To determine the optimal amount of rejuvenator experiments were performed with 8%, 10% ir 14% rejuvenator by bitumen mass. The effect of rejuvenators were evaluated by studying the main physical properties of bitumen: penetration and softening temperature. Ina n experimental study, aromatic oil was found to be more than 2.5 times more effective than soft bitumen.